2020
DOI: 10.1093/brain/awaa248
|View full text |Cite
|
Sign up to set email alerts
|

Predicting future rates of tau accumulation on PET

Abstract: Clinical trials with anti-tau drugs will need to target individuals at risk of accumulating tau. Our objective was to identify variables available in a research setting that predict future rates of tau PET accumulation separately among individuals who were either cognitively unimpaired or cognitively impaired. All 337 participants had: a baseline study visit with MRI, amyloid PET, and tau PET exams, at least one follow-up tau PET exam; and met clinical criteria for membership in one of two clinical diagnostic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
94
1
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 86 publications
(114 citation statements)
references
References 101 publications
17
94
1
2
Order By: Relevance
“…On the other hand, a previous longitudinal tau PET study did not find any significant APOE-ε4 effect on regional tau accumulation rates in CU individuals from the Berkeley aging cohort, although this negative finding could be related to the relatively low number of ε4 carriers in that study [64]. Finally, a recent longitudinal tau PET study found no APOE-ε4 effect on tau accumulation rates among CU individuals after controlling for baseline Aβ load [65]. However, the study reported a marginally significant independent APOE-ε4 effect on higher tau accumulation rates in a group of cognitively impaired individuals, but the interpretation of this finding is complicated by the mixed clinical composition of this group that included patients with MCI as well as typical and atypical AD dementia phenotypes.…”
Section: Discussionmentioning
confidence: 56%
“…On the other hand, a previous longitudinal tau PET study did not find any significant APOE-ε4 effect on regional tau accumulation rates in CU individuals from the Berkeley aging cohort, although this negative finding could be related to the relatively low number of ε4 carriers in that study [64]. Finally, a recent longitudinal tau PET study found no APOE-ε4 effect on tau accumulation rates among CU individuals after controlling for baseline Aβ load [65]. However, the study reported a marginally significant independent APOE-ε4 effect on higher tau accumulation rates in a group of cognitively impaired individuals, but the interpretation of this finding is complicated by the mixed clinical composition of this group that included patients with MCI as well as typical and atypical AD dementia phenotypes.…”
Section: Discussionmentioning
confidence: 56%
“…We did not find an effect of local amyloid-PET on FDG-PET, which is consistent with other cohorts of amyloid-positive individuals. 5,[31][32][33][34][35] Given that the degree of amyloid pathology reaches a plateau soon after symptom onset 76 in contrast with the increasing levels of tau pathology, 77,78 it is likely that any direct influence from amyloid plaque pathology may be difficult to detect given the neurotoxicity of tau pathology at this symptomatic stage.…”
Section: Discussionmentioning
confidence: 99%
“…The AD pathology that best correlates with the cognitive phenotype is neurofibrillary change related to tau pathology (Jack et al, 2019;Morris and Price, 2001;Pereira et al, 2019). The earliest neurofibrillary changes in typical AD are found in MTL structures, particularly the perirhinal cortex, which has a strong functional relationship to the hippocampus (Braak and Braak, 1991;Khan et al, 2014).…”
Section: Mechanism 4: Interaction Between Brain Activity Related To Auditory Cognition and Dementia Pathologymentioning
confidence: 99%
“…Finally, hearing loss may also affect the mechanisms for auditory grouping and segregation in the posterior neocortex and predispose to another AD variant: posterior cortical atrophy (Firth et al, 2019). Increasingly, clinical work has used biomarkers of AD pathology in cerebrospinal fluid (Jack and Holtzman, 2013) and brain imaging of biomarkers (Jack et al, 2019;Morris et al, 2016;Pereira et al, 2019) to provide estimates of the extent and distribution of disease. In research studies of incident dementia related to hearing loss, amyloid and tau imaging in particular could allow the assessment of regional AD pathology related to possible models for the interaction between hearing loss and dementia pathology.…”
Section: Ll Open Accessmentioning
confidence: 99%